Kekosongan Hukum Terhadap Sosialisasi Pemilihan Legislatif Dan Pemilihan Presiden Yang Berkedok Kampanye - S, Laurensius Arliman (Universitas Sumatera Barat, 2023)
Abstract: Indonesia has undergone various stages in the development of its democracy, one of which is the General Election. The phenomenon that has emerged today is the lack of clarity in the law regarding the socialization of legislative and presidential elections, which is sometimes disguised as campaign activities. The existing legal vacuum results in a lack of supervision over this kind of outreach, which can affect the integrity of elections and make it difficult for the public to differentiate between outreach and campaign activities. This research uses normative legal research methods, which explore and analyze applicable legal norms, including the Election Law and related regulations, as well as examining related cases that have been held previously. The research results show that the KPU plays a role in regulating and supervising the implementation of elections, including supervising campaign and outreach activities that have the potential to damage the rules. Bawaslu, as an independent monitoring institution, has an important role in monitoring violations during the election process, including in terms of socialization disguised as a campaign. The results of the second research, in order to strengthen democracy and election integrity, joint efforts by the KPU and Bawaslu to supervise socialization are essential to maintain a legitimate and fair election process. Regional governments, as implementers of elections at the local level, must also play a role in supervising socialization in their areas. Installing an APK under the guise of APS is a violation of Regional Regulations so that the regional institution executing it is the Civil Service Police Unit, where controlling socialization props that are considered illegal or violating can be carried out according to the authority of the institution concerned referring to the Regional Regulation. With this joint effort, we can minimize the potential for legal vacuum and promote an election process that is transparent, fair, and in accordance with democratic principles.